Production of Calcium-Binding Proteins in Crassostrea virginica in Response to Increased Environmental CO2 Concentration - Richards, Mackenzie; Xu, Wei; Mallozzi, Amy; Errera, Reagan M.; Supan, John (Frontiers in Marine Science, 2018)
Biomineralization is the complex process by organisms produce protective and supportive structures. Employed by mollusks, biomineralization enables creation of external shells for protection against environmental stressors. The shell deposition mechanism is initiated in the early stages of development and is dependent upon the concentration and availability of calcium carbonate ions. Changes in concentrations of the critical ions required for shell formation can result in malformation of shells. As pCO2 concentrations in the atmosphere continue to increase, the oceans are becoming more acidified. This process, known as ocean acidification (OA), has demonstrated adverse effects on shell formation in calcifying organisms across taxa. Although OA is known to inhibit the shell deposition in mollusks, the impact of OA on the gene regulation of calcium deposition remains unknown. Here we show the responses of four calcium-binding protein genes, caltractin (cetn), calmodulin (calm), calreticulin (calr), and calnexin (canx), to CO2-derived OA using a Crassostrea virginica mantle cell (CvMC) culture model and a larval C. virginica model. These four genes were cloned from C. virginica and the three-dimensional structures of the proteins encoded by these four genes were fully characterized using homologue modeling methods. Although an acidified environment by increased atmospheric pCO2 (1000 ppm) did not result in significant effects on CvMC proliferation and apoptosis, lower environmental pH induced upregulations of all four calcium-binding protein genes in CvMCs. Similarly, increased pCO2 did not affect the growth of larval C. virginica in the early stages of development. However, elevated pCO2 concentrations enhanced the expression of these calcium-binding protein genes at the protein level. The four calcium-binding protein genes demonstrated responsive expression profiles to an acidified environment at both cellular and individual levels. Further investigation of these genes may provide insight into the molecular regulation of mollusk biomineralization under OA stress.